Biodiversité et équilibre du régime alimentaire - Hélène Pagezy (Revue d'ethnoécologie)
The article places the relationships between food, food strategies, diet and nutritional state back into an interdisciplinary context – ecological, anthropological and biological. It concerns both ntomba “castes” : the baOto, farmers and fishermen, who also hunt and harvest to a lesser extent ; and the baTwa pygmies, descending from hunters-gatherers, who sometimes fish in flooded forest. After a long contact period, these two populations came to speak the same language and follow the same rules but for minor variations. In 1970, when this field experience began, there was an obvious biodiversity. Isolation protected it from quick transformation.The article follows the various steps of setting up a family diet and then an individual diet. It is guided by the specificities of environmental, socio-cultural and socio-economical contexts. The creation of a diet able to face biological as well as socio-cultural needs was a real challenge. Nevertheless, these two castes were compatible in their food strategies, alliances, vassalage, sharing and exchanges; which have been a true asset, allowing them not to put all their eggs in one basket.